Uji Coba Tepung Oyek Pengganti Tepung Jagung Dalam Pembuatan Corn Flakes - Salim, Chairul; Sembiring, Vienna Artina; Saputro, Yogi (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2025)
This study aims to develop oyek flour as a substitute for corn flour in the production of corn flakes and to analyze the differences in taste, texture, and color between corn flakes made with oyek flour and those made with corn flour. The methods used in this study are organoleptic testing and hedonic testing to measure the product characteristics and consumer preferences for each sample. Data were collected through questionnaires and analyzed using SPSS version 25 with a T-test to determine the significance of differences. The results showed that, in the organoleptic test, corn flakes with oyek flour had significant differences in taste and texture compared to the control corn flakes, while color showed no significant difference. In the hedonic test, there were significant differences in taste and texture, but no significant difference in color. Based on these results, it can be concluded that oyek flour can replace corn flour as the base ingredient in corn flakes, especially in terms of taste and texture. Future research is recommended to explore variations in the processing of oyek flour to improve product quality and expand its application to other food products. Keywords: corn flakes, cassava, oyek flour